Diabetes Mellitus and Gestational Diabetes Mellitus (Journal of Paediatric Surgeons of Bangladesh, 2015)
Diabetes mellitus (DM), also known as simply diabetes, is a group of metabolic diseases in which there are high blood sugar levels over a prolonged period. Worldwide in 2012 and 2013 diabetes resulted in 1.5 to 5.1 million deaths per year, making it the 8th leading cause of death. Diabetes overall at least doubles the risk of death. This high blood sugar produces the symptoms of frequent urination, increased thirst, and increased hunger. Untreated, diabetes can cause many complications. Acute complications include diabetic ketoacidosis and nonketotic hyperosmolar coma. Serious long-term complications include heart disease, stroke, kidney failure, foot ulcers and damage to the eyes. The number of people with diabetes is expected to rise to 592 million by 2035. The economic costs of diabetes globally were estimated in 2013 at $548 billion and in the United States in 2012 $245 billion. [3]Globally, as of 2013, an estimated 382 million people have diabetes worldwide, with type 2 diabetes making up about 90% of the cases. This is equal to 8.3% of the adults population, with equal rates in both women and men. There are three main types of diabetes mellitus: In case of type 1 Diabetes mellitus, results from the bodys failure to produce enough insulin. This form was previously referred to as insulin-dependent diabetes mellitus (IDDM) or juvenile diabetes. The cause is unknown. Another type is type 2 diabetes mellitus begins with insulin resistance, a condition in which cells fail to respond to insulin properly. As the disease progresses a lack of insulin may also develop. This form was previously referred to as non insulin-dependent diabetes mellitus (NIDDM) or adult-onset diabetes. The primary cause is excessive body weight and not enough exercise. Gestational diabetes is the third main form and occurs when pregnant women without a previous history of diabetes develop a high blood glucose level. Gestational diabetes usually resolves after the birth of the baby. It occurs in about 210% of all pregnancies and may improve or disappear after delivery. However, after pregnancy approximately 510% of women with gestational diabetes are found to have diabetes mellitus, most commonly type 2. Gestational diabetes is fully treatable, but requires careful medical supervision throughout the pregnancy.J. Paediatr. Surg. Bangladesh 5(1): 30-35, 2014 (January)